Majas Dalam Lirik Lagu Opick Album Cahaya Hati: Tinjauan Stilistika - Mujiatti, Mujiatti (Puitika, 2022)
Penelitian ini dilakukan untuk menjelaskan majas pada lirik lagu Opick album Cahaya Hati. Tujuan  penelitian ini adalah untuk (1) mengetahui bentuk majas yang terdapat dalam lirik lagu Opick album Cahaya Hati, (2) mengetahui makna majas dalam lirik lagu Opick album Cahaya Hati.Berdasarkan hasil analisis, ditemukan bahwa kelima lagu Opick pada album Cahaya Hati memiliki lima jenis majas, yaitu majas aliterasi, asonansi, personifikasi, metafora, dan majas hiperbola. Majas asonansi terdapat sebanyak 13 majas, majas aliterasi terdapat sebanyak 7 majas, Majas metafora terdapat sebanyak sepuluh majas, majas hiperbola terdapat sebanyak satu majas, dan majas personifikasi sebanyak 4 majas.  This research was conducted to explain the figure of speech in the lyrics of the song Opick album Cahaya Hati. The purpose of this study was to (1) determine the form of figure of speech contained in the lyrics of the song Opick album Cahaya Hati, (2) find out the meaning of the figure of speech in the lyrics of the song Opick album Cahaya Hati.Based on the results of the analysis, it was found that the five Opick songs on the Cahaya Hati album have five types of figure of speech, namely alliteration figure of speech, assonance, personification, metaphor, and hyperbole figure of speech. There are 13 assonance figures of speech, 7 alliteration figures of speech, ten of metaphorical figures of speech, one hyperbole figure of speech, and 4 personifications of personification.